Cal Poly alumnus Captain Robert Gibson shaking hands with cosmonaut counterpart Vladimir N. Dezhurov while weightless in space - National Aeronautics and Space Administration (NASA)::::::::: (1995)
Weightless in space, Gibson shakes hands with his Cosmonaut counterpart, Vladimir N. Dezhurov, after successfully docking the Space Shuttle Atlantis to Mir for the first time on June 29, 1995.